Les Conservateurs écossais et les élections de 2017 à la Chambre des Communes : succès éphémère ou détoxification durable ? - Edwige Camp-Pietrain (Revue Française de Civilisation Britannique, 2018)
At the general election held on June 8 2017, the Scottish Conservatives who had only had one seat in the House of Commons since 2001 gained 13 MPs thanks to a twofold increase in their share of the vote . This recovery was put down to their leader Ruth Davidson. This article argues that although the latter's efforts should not be underestimated she has benefited from work undertaken under her predecessor and she has taken full advantage of the context, ie the resurgence of Scotland's constitutional issues with the prospect of Brexit. She now faces another challenge as her MPs will have to prove that they can defend Scottish interests.